2018
DOI: 10.2478/foecol-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Soils classified in the Arboretum Mlyňany, Slovakia

Abstract: Successful adaptation of introduced trees requires providing appropriate conditions for their growth and life. In this context, our study aim was a soil survey in the Arboretum Mlyňany, on the basis of which the soils could be classified. Detailed soil investigations were done at seventeen sites under dense monocultures of trees and the grassland. For each site, there was dug one soil pit, near which there were made three soil bores. Over most area of the locality, the prevailing soil-forming substrates were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…1. According to the work of Polláková (2018), in the area of the experimental field, luvic chernozem is indicated.…”
Section: Study Site and Biological Materialsmentioning
confidence: 99%
“…1. According to the work of Polláková (2018), in the area of the experimental field, luvic chernozem is indicated.…”
Section: Study Site and Biological Materialsmentioning
confidence: 99%
“…For this experiment, seven sampling sites were chosen with the intention to include all soils classified at area of Arboretum [Polláková 2018 Undisturbed soil samples (100 cm 3 ) were collected in three repetitions using steel cylinders per each of 0.1 m layer to the depth of 0.8 or 0.9 m. In laboratory, the physical properties were determined using standard analytical methods [Kobza et al 2011]. The results of physical data are detailed in Polláková et al [2017].…”
Section: Soil Sampling and Analysesmentioning
confidence: 99%
“…In some parts of the arboretum, there are also podzolic soils (Tábor and Pavlačka, 1992). In a recent study, Polláková (2018) identified three reference soil groups (RSG) in the Mlyňany Arboretum, namely luvisols, retisols and chernozems.…”
Section: Mlyňany Arboretum Ife Sasmentioning
confidence: 99%